Variasi Fonologi dan Morfologi Bahasa Lematang di Desa Raja Jaya Kabupaten Pali - Sari, Erna Purnama; Agustina, Juaidah; Masnunah, Masnunah (PPSDP Undergraduate Journal of Educational Sciences, 2025)
This research aims to determine variations in phonology and morphology of the Lematang language in Raja Jaya village, Pali district. Regional languages ​​are part of the Indonesian culture that lives and develops in society, including regional languages ​​in Raja Jaya Village. The goal that this research wants to achieve is what form the Lematang language exists in Raja Jaya Village. Data collection techniques in this research are listening, taking notes and recording. Data analysis uses qualitative descriptive. The research method used is a qualitative descriptive method with an approach to analyzing and interpreting regional language data. The results of the research carried out were several vowel phonemes, changes in phoneme sounds, addition of phoneme sounds, release of phoneme sounds, free morphemes and bound morphemes. There are several forms of phonemes and morphemes and there are several changes and errors in pronunciation when delivering a sentence by speakers in the Raja Jaya village community.